Management of limb length problems during total hip arthroplasty for patients with developmental dysplasia of the hip. (2nd July 2020) - Benjamin, Biju; Haddad, Fares S
Abstract : The anatomy of the acetabulum and femur is usually significantly altered in people with developmental dysplasia of the hip and this leads to secondary osteoarthritis of the hip joint. Ideal positioning of implants and reduction of the joint is technically demanding during arthroplasty. Lengthening may result in nerve palsies and therefore procedures may have to be undertaken to shorten the femur. Other complications include dislocation and non-union at the shortening osteotomy site. Thorough preoperative planning and templating is required before surgery to assess the need for shortening. Shortening osteotomies can be performed at the proximal femur, diaphysis or distal femoral levels, with subtrochanteric being the most common level. The procedure should be customised for each patient after extensive planning and detailed counselling.